GAMBARAN TINGKAT PENGETAHUAN IBU HAMIL TENTANG PEMBERIAN ASI EKSKLUSIF DALAM PEMENUHAN GIZI BAYI UMUR 0-6 BULAN - Elizabeth Septianur Girsang; Dina Keumala Sari; Endy Juli Anto (Universitas Methodist Indonesia, 2018)
Background. Exclusive breastfeeding has many benefits for babies, including babies getting a complete source of nutrition, babies protected from gastrointestinal infections, increasing immunity, reducing death rates caused by various diseases, besides breastfeeding can increase intelligence including spiritual intelligence , maintaining the growth and development of the baby's brain. The provision of ASI has not been utilized optimally by mothers, this is due to several factors including the low level of understanding of exclusive breastfeeding due to lack of information or knowledge possessed by mothers regarding all values plus nutrients and benefits contained in breast milk. This study aims to describe the knowledge of pregnant women about exclusive breastfeeding in fulfilling nutrition for infants aged 0-6 months in Tanjung Rejo Village, Medan Sunggal Subdistrict, 2017. Methods. This study used a descriptive research method with a cross sectional design. This research was conducted on 31 October 2016-20 July 2017. The sample size was 63 people using the Total Sampling method. Methods of collecting data using a questionnaire. Processing data by editing, coding, entry, cleaning and tabulating. Data analysis using univariate analysis. Result. The results of the study showed that there were 18 respondents (28.6%) good levels of knowledge, there were enough 40 people (63.5%) and less than 5 people (7.9%). Summary. Respondents knowledge about level of knowledge of giving the majority of exclusive breastfeeding is quite good.